CICHORIUM INTYBUS LINN: A REVIEW OF PHARMACOLOGICAL PROFILE - Saxena, Rahul; Sulakhiya, Kunj Bihari; Rathore, Manoj (International Journal of Current Pharmaceutical Research, 2014)
The use of natural products as medicinal agents presumably predates the earliest recorded history. Cichorium Intybus L. is a plant which is used in several traditional medicine systems to cure various diseases Chicory belongs to the family Asteraceae is a small aromatic biennial or perennial herb. This plant has been known to posses Anti-ulcer, Hepatoprotective, Antibacterial, Cardioprotective, Antioxidant and Free radical Scavenging, Anti-malarial, Anti-fungal, Gastroprotective, Antihelminthic, Analgesics, Tumour protective, Anti-allergic and other miscellaneous activities. The whole plant contains a number of medicinally important compounds showing therapeutic effects such as inulin, esculin, volatile compounds, bitter sesquiterpene lactones, coumarins, flavonoids and vitamins etc. The pharmacological studies reported in the present review confirm the therapeutic value of Chichorium Intybus L. Thus the use of this plant for human and animal disease therapy and reinforce the importance of the ethno-botanical approach as a potential source of bioactive substances.